Elevated Procalcitonin Levels in Pediatric Severe Bacterial Pneumonia Caused by Klebsiella pneumoniae - Kusumawijayanti, Tri; Putra, David Anggara; Hafidh, Yulidar; Andarini, Ismiranti (Cell and BioPharmaceutical Institute, 2025)
Background: Klebsiella pneumoniae is a major pathogen in pediatric pneumonia. Procalcitonin (PCT) distinguishes between Gram positive and Gram negative infections but lacks data on K. pneumoniae infection's relationship with PCT levels in children. Therefore, this study was conducted to investigate the serum PCT levels in children with K. pneumoniae infection.Materials and methods: A cross-sectional study was conducted on 61 pediatric subjects with the age of 2-59 months with severe bacterial pneumonia. Blood and sputum samples were collected and analyzed for PCT and cultured for 24 hours. PCT levels and K. pneumoniae infection were statistical analyzed with chi-square and logistic regression. Receiver operating characteristic (ROC) analysis was used to determine the PCT cut-off specific to K. pneumoniae. Results: K. pneumoniae was identified in 33%. Median PCT levels were significantly higher in the K. pneumoniae group (p<0.05). A PCT cut-off of 0.725 ng/mL yielded 70% sensitivity, 70.7% specificity, negative predictive value (NPV) of 82.9%, and area under the receiver operating characteristic curve (AUROC) of 0.74. Elevated PCT was significantly associated with K. pneumoniae infection with Odds ratio (OR) of 12.08, 95% Confidence Interval (CI): 2.54-57.36; p=0.002).Conclusion: Along with K. pneumoniae infection, serum PCT levels was elevated, supporting its potential as a biomarker for early diagnosis. Keywords: K. pneumoniae, procalcitonin, bacterial pneumonia, pediatric